Social housing as a social opportunity and the importance for the development of the municipality of Ijuí/RS (Research, Society and Development, 2020)
This article has as its theme to understand what social housing and what benefits it offers to society for the development of the municipality of Ijuí / RS, thus contributing to the discussions about. The concern we have for those most in need and the search for the right to decent housing, are actions that refer a lot to assistance, both from the government and the community, this theme came up with the aim of demonstrating the reality of the houses, and how much this phenomenon has contributed to the regional growth of the municipalities. Families that are often evicted from their homes or from irregular settlements end up experiencing subhuman needs and conditions to survive. The research is based on objective 11 of the 2030 Agenda (UN 2015), to make cities and human settlements inclusive, safe, resilient and sustainable. Which refers to Sustainable Cities and Communities, and highlights the importance of making cities and human settlements inclusive, safe, resilient and sustainable. It is understood that it is from these relationships, studying the contributions of the Housing programs, that one can enter into the search for solutions and information to improve the human and territorial conditions of cities.